Enemies and Friends: A Consideration of the Burnham Kidnapping - Burns, Gerald T. (Archīum Ateneo, 2024)
The relationships between the political and the spiritual, hostage-taker and victim, friends and enemies, the US and the Philippines are shaped and contested in the light of journalistic accounts of the Burnhams’ hostage crisis in 2001, and in particular Gracia Burnham’s reconstruction of it in her memoir. The following four distinct but related contexts are used as lens to explore the binarisms: 1) the psychosocial dynamics and literary traditions of captivity; 2) what used to be billed the “special” but has more recently and perhaps more accurately been called the “entangled” relationship between the United States and the Philippines; 3) the geopolitics of the “War (of and on) Terror” that broke out with full force during the Burnhams’ hostage days, and/or of the longer-term “clash of civilizations,” as it is sometimes called, between militant Islam and the globalizing Judeo-Christian West; and 4) the historic resurgence, in many areas of the world, of religion in personal and public life.